CT Imaging Findings after Stereotactic Radiotherapy for Liver Tumors. (29th June 2015) - Brook, Olga R.; Thornton, Eavan; Mendiratta-Lala, Mishal; Mahadevan, Anand; Raptopoulos, Vassilious; Brook, Alexander; Najarian, Robert; Sheiman, Robert; Siewert, Bettina
Abstract : Purpose . To study radiological response to stereotactic radiotherapy for focal liver tumors. Materials and Methods . In this IRB-approved, HIPAA-compliant study CTs of 68 consecutive patients who underwent stereotactic radiotherapy for liver tumors between 01/2006 and 01/2010 were retrospectively reviewed. Two independent reviewers evaluated lesion volume and enhancement pattern of the lesion and of juxtaposed liver parenchyma. Results . 36 subjects with hepatocellular carcinoma (HCC), 25 with liver metastases, and seven with cholangiocarcinoma (CCC) were included in study. Mean follow-up time was 5.6 ± 7.1 months for HCC, 6.4 ± 5.1 months for metastases, and 10.1 ± 4.8 months for the CCC. Complete response was seen in 4/36 (11.1%) HCCs and 1/25 (4%) metastases. Partial response (>30% decrease in long diameter) was seen in 25/36 (69%) HCCs, 14/25 (58%) metastases, and 7/7 (100%) of CCCs. Partial response followed by local recurrence (>20% increase in long diameter from nadir) occurred in 2/36 (6%) HCCs and 4/25 (17%) metastases. Liver parenchyma adjacent to the lesion demonstrated a prominent halo of delayed enhancement in 27/36 (78%) of HCCs, 19/21 (91%) of metastases, and 7/7 (100%) of CCCs. Conclusion . Sustainable radiological partial response to stereotactic radiotherapy is most frequent outcome seen in liver lesions. Prominent halo of delayed enhancement of the adjacent liver is frequent finding.